Gender differentials in value addition and lean season market participation in the grasshopper value chain in Uganda - Emmanuel, Donkor; Robert, Mbeche; Dagmar, Mithöfer (John Wiley & Sons, Ltd, 2022)
Abstract Gender gaps in agrifood value chains are manifested in differential access to and control of productive resources, upgrading activities, market participation, farm productivity and food security among women and men. These gender gaps threaten economic development in sub-Saharan Africa. With low-resource requirements, edible insects have emerged as a promising agrifood value chain with income opportunities for women and men. However, it is not clear how gender gaps are manifested in the participation in value addition and lean season market of the edible insect value chain with a potential to improve household welfare. In this paper, we analyse the gender gaps of retailers' participation in value addition and lean season market in the grasshopper value chain in Uganda. Multivariate probit and tobit models are used in the empirical analyses. We find that women are 15% more likely to participate in primary value addition. However, there are no gender gaps in the participation in secondary value addition and the lean season market. The study also shows that grasshopper business is an important source of income for many retailers. Therefore, the development of the grasshopper value chain, especially the aspects of value addition and lean season market, could contribute to gender equality and improvement of livelihoods of women and men
Keywords: Agrifood sector, edible insect value chain, food security, gender gap, upgrading strategies, value addition